2021
DOI: 10.1152/ajpheart.00368.2021
|View full text |Cite
|
Sign up to set email alerts
|

Blunted peripheral but not cerebral vasodilator function in young otherwise healthy adults with persistent symptoms following COVID-19

Abstract: Recent findings suggest that COVID-19 causes vascular dysfunction during the acute phase of the illness in otherwise healthy young adults. To date, no studies have investigated the longer-term effects of COVID-19 on vascular function. Herein, we hypothesized that young, otherwise healthy adults who are past the acute phase of COVID-19 would exhibit blunted peripheral (brachial artery flow-mediated dilation (FMD) and reactive hyperemia) and cerebral vasodilator function (cerebral vasomotor reactivity to hyperca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 14 publications
5
84
0
2
Order By: Relevance
“…Thus, all participants were nonobese, normotensive, and young. Unlike the two previous studies ( 13 , 14 ), the current study only assessed microvascular function and therefore we cannot speculate whether macrovascular function would be altered in this cohort. Future investigations are needed to further elucidate the impacts of COVID-19 on micro and macrovascular function in older demographics, as well as those who have preexisting cardiovascular disease risk factors.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Thus, all participants were nonobese, normotensive, and young. Unlike the two previous studies ( 13 , 14 ), the current study only assessed microvascular function and therefore we cannot speculate whether macrovascular function would be altered in this cohort. Future investigations are needed to further elucidate the impacts of COVID-19 on micro and macrovascular function in older demographics, as well as those who have preexisting cardiovascular disease risk factors.…”
Section: Discussionmentioning
confidence: 84%
“…Although Ratchford et al ( 14 ) characterized vascular function in post-COVID-19 adults 3–4 wk post-infection, Nandadeva et al ( 13 ) did so in adults on average 13 wk post infection (range: 4–21 wk). In this study, participants were tested in a range of 12 days to 357 days post-diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent analysis revealed that peripheral macrovascular and microvascular vasodilation was significantly reduced in young adults still being symptomatic, while asymptomatic participants had similar vascular function compared with controls. Cerebral vascular function and central arterial stiffness were unaffected irrespective of COVID-19 symptoms persisting or not ( Nandadeva et al, 2021 ).…”
Section: Long-covid Syndrome (Lcs) In Cvdmentioning
confidence: 99%